The Luxembourgish Steel Industry in the Cold War: Diplomacy in the Wake of Nationalizations. (2nd September 2015) - Birchen, Marc
Abstract : Contrary to the common narrative, Luxembourgish post-war foreign policy was not limited to the European integration process. In fact, the country's largest diplomatic focus regarding Eastern Europe in the first years after the Second World War dealt with the protection of the assets of Arbed, Luxembourg's largest steel company. This article provides a case study on the effects of Cold War socio-economic developments on an internationally operating company. It also analyses Luxembourg's East-West interconnectedness, and its scope of action aimed at the protection of its business interests in Eastern Europe. Based on an analysis of the communication between Arbed, the Luxembourgish authorities, and their Western and Eastern counterparts, this article reveals the importance of private and public East-West exchanges for Luxembourg, as well as the historic founding of these exchanges, which dates back to the inter-war years. It thus stresses the continuity of these connections throughout the war years, despite the ever-changing geopolitical and politico-economic realities.